Use of the Padlet Platform in Online Learning Media in Higher Education - Kayoko Nozaki; Matsuzaki Wuttipong; Heman Hiroyuki (Yayasan Adra Karima Hubbi, 2023)
Background. Students who are constrained in conducting face-to-face lectures so they cannot go to campus for other reasons, cannot carry out the learning process with lecturers and lecturers cannot also provide material to students so that the teaching and learning process is hindered because they cannot meet. This problem may be caused by the lack of innovation in the series of learning carried out in tertiary institutions. Purpose. of this research is to search for information from students in tertiary institutions about the use of padlets. Method. used is a qualitative method in which the research uses it as a guide so that the focus of the research is in accordance with the facts in the field and data that contains numbers so that the data can be formed by using the Google form as a means to make a questionnaire of questions given to correspondents who can used as a research subject, besides that the theoretical basis is also useful to provide an overview of the research setting and as material for research discussion. Results. of this study are to provide that there is progress in using the padlet platform in learning this lecture in tertiary institutions. Conclusion. of this study is that the use of the padlet platform makes it easier for students to study at tertiary institutions online through information and communication technology learning media, and others